2020
DOI: 10.1111/idj.12515
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between orthodontic treatment and dental caries: results from a national survey

Abstract: Objectives Orthodontic treatment has been suggested to increase the risk of dental caries. The aim of this study was to evaluate the association between orthodontic treatment and the likelihood of dental caries. Methods The study included data for adults aged ≥ 19 years who participated in the Korea National Health and Nutrition Examination Survey in 2013–2015. The participants’ demographic, socio‐economic, and general and oral health‐care data were collected by trained interviewers using a structured question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 31 publications
3
18
0
2
Order By: Relevance
“…Most of those studies(18-21) had questionable methodological quality attributable to numerous reasons, including convenient sampling with inherent selection bias, insu cient sample sizes leading to false-negative results (i.e., type II error), incorrect statistical procedures such as parametric analyses on non-normally distributed dependent variables such as DFT components and aggregates, lack of control for confounding factors, and no accountability for dental caries severity. Two studies (20,21) were in agreement with this study's ndings showing a signi cant protective association between a previous history of orthodontic treatment and untreated caries (i.e., DT) later in life, whereas one other study (18) found no signi cant association. Only two studies (18,20) investigated the effect of a previous history of orthodontic treatment on the number of FT and found no signi cant associations, which contradicts the present nding of positive association.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Most of those studies(18-21) had questionable methodological quality attributable to numerous reasons, including convenient sampling with inherent selection bias, insu cient sample sizes leading to false-negative results (i.e., type II error), incorrect statistical procedures such as parametric analyses on non-normally distributed dependent variables such as DFT components and aggregates, lack of control for confounding factors, and no accountability for dental caries severity. Two studies (20,21) were in agreement with this study's ndings showing a signi cant protective association between a previous history of orthodontic treatment and untreated caries (i.e., DT) later in life, whereas one other study (18) found no signi cant association. Only two studies (18,20) investigated the effect of a previous history of orthodontic treatment on the number of FT and found no signi cant associations, which contradicts the present nding of positive association.…”
Section: Discussionsupporting
confidence: 88%
“…Identi cation of the factors that contribute to high caries susceptibility will allow clinicians and public health personal to e ciently apply targeted prevention, which has been recognized to be a cost-effective approach (36). Despite previous efforts by scholars to examine the association between the history of previous orthodontic treatment and caries development later in life (18)(19)(20)(21), none of the reported studies accounted for the highly caries-susceptible individuals (i.e., those with DT > 2, FT > 11, and DFT > 12 in this study population). This cross-sectional study intended to ll this gap in the current literature by using population-based data to comprehensively assess the effect of orthodontic treatment on dental caries experience, prevalence, and severity later in life by using a sample representative of U.S. adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations